Solve for x: 2x−4x−3=−27.

1 answer

To solve for x, we first simplify the left side of the equation:

2x - 4x - 3 = -27
-2x - 3 = -27
-2x = -27 + 3
-2x = -24

Next, we divide both sides by -2 to solve for x:

x = -24 / -2
x = 12

Therefore, the solution to the equation 2x - 4x - 3 = -27 is x = 12.
Similar Questions
  1. Combine like terms:-3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x: 8x-11= -11x+18 Solve for x: -2(x-5)+7=z-8-5x Solve for x: (x-2)/5 -
    1. answers icon 8 answers
  2. Solve the indicated variable:1. Volume of a cone: solve for h: V=¨ir^2h/3 2. Temperature formula: solve for C: F=9/5C+32
    1. answers icon 1 answer
  3. Put in the correct orderSolve exponentiation. Solve multiplication and division. Solve operations within parentheses Solve
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions